Robust Battery Capacity Optimization of Off-Grid PV Systems for Dynamic Load Uncertainty - YUSIRAN YUSIRAN; FAUZUN ATABIQ (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
Off-grid solar power systems face fluctuating loads, complicating battery sizing. This study applies Monte Carlo simulation with the bootstrap method to optimize battery capacity for an 8.12 kWp PV system. Data include 113-day aggregated data and four high-resolution (5-minute) load profiles. 5,000 bootstrap scenarios were simulated over a capacity range of 16–48 kWh, targeting a probability of achieving a self sufficiency ratio (SSR) above 80%. Results indicate that a 30 kWh capacity achieves P(SSR > 80%) = 95.1%, meeting the target, while 32 kWh yields a marginal increase (95.8%). Diminishing return analysis shows that beyond 30–32 kWh, each additional 2 kWh improves probability by less than 0.5%. The technically optimal capacity is 30–32 kWh. Validation using high-resolution data confirms that a 16 kWh battery is safe for normal loads (lowest SOC = 27%) but proves insufficient under extreme conditions, with SOC dropping to 14%.